Photocatalytic degradation of VOCs from air stream using Mo:TiO2/GAC nanocomposites - Kamaladdin Abedi; Behzad Shahmoradi; Ebrahim Mohammadi; Kitirote Wantala; Afshin Maleki; Yahya Zandsalimi; Sonya Salimi; Shadi Kohzadi (Materials Research Express, 2022)
Modification of TiO _2 is one of the techniques used to enhance its photodegradation efficiency and to make it visible-light-active. In this study, Mo-doped TiO _2 nanoparticles were synthesized using a fast sol-gel technique and then coated on granular activated carbon (GAC) as both substrate and adsorbent to obtain Mo:TiO _2 /GAC composite. The fabricated composite was characterized by many techniques such as powder XRD, SEM, EDX, FTIR, and N _2 adsorption-desorption analysis. Then, the composite was applied to photodegrade volatile organic compounds (VOCs) under both UV and visible light irradiations. The characterization results showed high crystallinity and purity. Mo:TiO _2 /GAC composite gave a higher photodegradation efficiency compared with bare TiO _2 and bare GAC. Moreover, studying operational parameters showed that the optimum condition for photodegradation efficiency of VOCs was at a flowrate of 1 L min ^−1 , VOCs concentration of 20 ppm, and light intensity of 400 and 600 W m ^−2 for UV and visible light, respectively. The results suggest that Mo:TiO _2 /GAC is a visible-light-active composite and can be acceptably used to decompose VOCs under visible light with adequate efficiency and without the generation of harmful by-products such as O _3 as compared with UV.